The association between EPCR gene p.Ser219Gly polymorphism and venous thromboembolism risk: a case–control study, meta-analysis, and a reproducibility study - Pituk, Dóra; Miklós, Tünde; Schlammadinger, Ágota; Rázsó, Katalin; Bereczky, Zsuzsanna (Frontiers in Cardiovascular Medicine, 2023)
Background The rs867186 single-nucleotide polymorphism in the PROCR gene (g.6936A > G, c.4600A > G) results in a serine-to-glycine substitution at codon 219 of endothelial protein C receptor (EPCR). We performed a case–control study followed by an updated meta-analysis of the association between this polymorphism and the risk of venous thromboembolism (VTE). Objective and methods We enrolled 263 VTE patients and 320 unrelated healthy controls for the case–control study. The total number of cases and controls for the meta-analysis were 5,768 and 30,017, respectively. A new online MetaGenyo Statistical Analysis System software was used to perform the current meta-analysis. Furthermore, a reproducibility study was conducted to validate our results. Results Among well-defined thrombosis risk factors, Factor V Leiden was more frequent in the VTE group (p < 0.001), while there was no difference in mutation frequency of prothrombin 20210G>A polymorphism between the two groups. There was no difference in the mutation frequency of Factor V Leiden and prothrombin 20210G>A between cases with and without provoking factors and cases with and without VTE recurrence. The rs867186 “G” carriership did not influence the risk of VTE [odds ratio (OR) 1.339; 95% confidence interval (CI): 0.904–1.984] in our study. No significant differences could be demonstrated among the rs867186 genotype frequencies between VTE cases with and without provoking factors (p = 0.430). PROCR rs867186 was associated with an OR of 1.72 (95% CI: 0.95–3.13, p = 0.075) in terms of VTE recurrence. In the meta-analysis, a significant association was found between EPCR Ser219Gly polymorphism and VTE under the dominant model (OR = 1.27, 95% CI: 1.11–1.46, p = 0.0006), the recessive model (OR = 1.60, 95% CI: 1.26–2.04, p = 0.0001), the GG vs. AA contrast model (OR = 1.64, 95% CI: 1.28–2.09, p = 0.0001), and the GA vs. AA contrast model (OR = 1.24, 95% CI: 1.08–1.43, p = 0.002). Conclusion The rs867186 was not associated with the first VTE risk in our case–control study; however, a tendency to VTE recurrence was observed. Based on the results of our reproducibility study, MetaGenyo is acceptable for meta-analysis in case of genetic epidemiology studies. Although the risk conferred by the rs867186 is mild in all meta-analyses, including ours, identifying patients carrying the minor allele might have an impact on personalized VTE risk assessment, risk-score calculation, and patient management.